Religieuse ervaring: Aspoestertjie van teologiese besinning - Veldsman, D. P. (Hervormde teologiese studies, 1990)
Religious experience: Cinderella of theological Reflection How is the concept ‘experience’ to be understood, a concept frequently used but which defies clearcut definition? How is religious experience, which is not a terminus technicus, to be understood? These questions are addressed from a historic survey of developments in the interpretation of the nature and understanding of religious experience, spanning Aristotle to modern German theologians. Stressing the fundamental importance for theology of reflection on religious experience, this article describes religious experience as feeling plus a religious conceptual framework, constituted by recollection and embodied in hope.